Hafnium in nuclear power industry: the evolution of increasing of the economic indicators and the operation safety of pressurized water nuclear reactors - Shilyaev, B.A.; Ulybkin, A.L.; Kovtun, K.V.; Rybka, A.V.; Kutny, V.E.; Pudov, A.O. (Вопросы атомной науки и техники, 2018)
А further increase of the reliability, safety and efficiency of nuclear reactors, the extension of the nuclear fuel campaign and a better control of the fuel burning-out level demand to search for and use new materials. New materials are also necessary for new energy release management elements in the active zone. In this paper, the potential place that hafnium could occupy in the solution of the mentioned tasks is discussed. The high values of the absorption cross-section for thermal and epithermal neutrons, high corrosion resistance, good mechanical properties and heat conduction of hafnium allow for its use, without any barrier coatings, as the absorbing and structural material for regulation rods of nuclear reactors. Another application of high purity hafnium in the nuclear power industry can be in the emitter material of Compton-type Self-Powered Neutron Detectors (SPND). Such SPND will have instant response to neutron flux changes, which will allow to reach positive effects on the reactor safety and efficiency: increase fuel burning-out times; control the crisis boiling coordinates and time; exclude the processes, which could cause heavy accidents).